Respuesta :

Answer:

Step-by-step explanation:

2) x - y = 2/3

         [tex]x = \frac{2}{3} + y[/tex]

3) 3x +2y = 6

          3x = 6 - 2y

Divide the equation by 3

[tex]\frac{3x}{3}=\frac{6}{3}-\frac{2y}{3}\\\\x = 2 - \frac{2}{3}y[/tex]

4)

[tex]\frac{1}{4}x + y = 2\\\\ y = 2 - \frac{1}{4}x[/tex]

5) 4x - 3y = -33

         -3y = -33 - 4x

Divide the equation by (-3)

[tex]\frac{-3}{-3}y=\frac{-33}{-3} - \frac{4}{-3}x\\\\ y = 11 + \frac{4}{3}x[/tex]

1) Yes, it was easy to solve one variable in terms of the other.

2) Yes, it was easy to solve for y in terms of x. Coefficient of x was a fraction.

3) It will be easy if we take the value of x as multiples of 3

Example: if x = 3,

[tex]y = 11 + \frac{4}{3}*3 \\\\y = 11 + 4\\\\y = 15[/tex]

It is easy to plot (3 ,15)